Wheat genome architecture influences interactions with phytobeneficial microbial functional groups in the rhizosphere. (28th December 2022) - Gruet, Cécile; Abrouk, Danis; Börner, Andreas; Muller, Daniel; Moënne‐Loccoz, Yvan
Abstract: Wheat has undergone a complex evolutionary history, which led to allopolyploidization and the hexaploid bread wheat Triticum aestivum . However, the significance of wheat genomic architecture for beneficial plant–microbe interactions is poorly understood, especially from a functional standpoint. In this study, we tested the hypothesis that wheat genomic architecture was an overriding factor determining root recruitment of microorganisms with particular plant‐beneficial traits. We chose five wheat species representing genomic profiles AA ( Triticum urartu ), BB SS ( Aegilops speltoides ), DD ( Aegilops tauschii ), AABB ( Triticum dicoccon ) and AABBDD ( Triticum aestivum ) and assessed by quantitative polymerase chain reaction their ability to interact with free‐nitrogen fixers, 1‐aminocyclopropane‐1‐carboxylate deaminase producers, 2, 4‐diacetylphloroglucinol producers and auxin producers via the phenylpyruvate decarboxylase pathway, in combination with Illumina MiSeq metabarcoding analysis of N fixers (and of the total bacterial community). We found that the abundance of the microbial functional groups could fluctuate according to wheat genomic profile, as did the total bacterial abundance. N fixer diversity and total bacterial diversity were also influenced significantly by wheat genomic profile. Often, rather similar results were obtained for genomes DD ( Ae. tauschii ) and AABBDD ( T. aestivum ), pointing for the first time that the D genome could be particularly important for wheat–bacteria interactions. Summary statement: Genome D is important for rhizosphere interactions of wheat with phytobeneficial microbial functional groups.